2017
DOI: 10.1007/s40089-017-0207-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of zinc oxide nanoparticles using terpenoid fractions of Andrographis paniculata leaves

Abstract: Zinc oxide (ZnO) nanoparticles have been widely employed for various pharmacological applications. Several approaches were tried to synthesize ZnO nanoparticles. In this study, ZnO nanoparticles were biosynthesized using terpenoid (TAP) fractions isolated from Andrographis paniculata leaves. Subsequently, the ZnNO 3 (0.1 N) is treated with the isolated TAP fractions to biosynthesize zinc oxide nanoparticles (Zn-TAP NPs). This nanoparticle preparation has been confirmed by the colour change from green to cloudy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 18 publications
4
19
0
Order By: Relevance
“…Moreover, some of the bacterial cells were shown to change shape from rod-shaped to slightly coccus-shaped, while others decreased in size or showed multiple dents on the cell surface ( Figure 3 D–F). The SEM findings are consistent with those reported previously [ 16 , 17 , 18 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, some of the bacterial cells were shown to change shape from rod-shaped to slightly coccus-shaped, while others decreased in size or showed multiple dents on the cell surface ( Figure 3 D–F). The SEM findings are consistent with those reported previously [ 16 , 17 , 18 ].…”
Section: Resultssupporting
confidence: 93%
“…The morphological changes of KPC before and after treatment were evaluated by SEM imaging. The results showed transformations in cell size and shape due to the effect of ZnO-NPs; these changes led to the loss of the integrity of the membrane and the death of the cell [ 16 ]. The most interesting finding was obtained in vivo because it confirmed the potential of ZnO-NPs to overcome KPC.…”
Section: Discussionmentioning
confidence: 99%
“…Highly monodispersed (18.24 nm) spherical Au NPs could be synthesized using kaempferol as the in situ reductant and stabilizer [ 141 ]. The ability of terpenoid fractions isolated from Andrographis paniculata leaves for the green synthesis of ZnO NPs has also been demonstrated and confirmed by the presence of C=O functional group in the NPs [ 142 ]. Au NPs were synthesized using chlorogenic acid as reductant, and the corresponding FT-IR spectra indicated that an –OH functional group was likely involved in the synthesis [ 143 ].…”
Section: Secondary Metabolites In Plant Extract-mediated Green Synmentioning
confidence: 99%
“…It is known that the ZnO nanoparticles have free electrons due to which Surface Plasmon Resonance (SPR) absorption band appear at 289.9 nm. This absorption peak indicates the reduction of Zn 2+ ions in the reaction medium which authenticates the formation of ZnO nanoparticles [4,11]. No other peaks have been observed which confirms the The energy band gap value is found to be 4.28 eV which is more than pure ZnO nanoparticles i.e., 3.4 eV.…”
Section: Characterizationmentioning
confidence: 54%